PENGEMBANGAN MODUL AJAR GEOGRAFI KELAS X KURIKULUM SEKOLAH PENGGERAK MATERI DINAMIKA LITOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN DI SMA NEGERI 5 KUPANG - Jurumana, Eman Umbu Siwa; Pamungkas, Bella Theo Tomi; Sunimbar, Sunimbar (Jurnal Geografi, 2023)
This study aims to (1) determine the changes in the curriculum at SMA Negeri 5 Kupang geography teaching module X (2) determine the development of the lithospheric dynamics teaching module and the impact on life in SMA Negeri 5 Kupang. The method used in this research is research and development (Research and Development). The curriculum have changed a lot at SMA Negeri 5 Kupang Since the school was founded in 1991, the 1994 curriculum, 1997 curriculum, Competency-Based Curriculum (2004-2013), Education Unit Level Curriculum (KTSP) 2006, Curriculum (2013) and Currently the “Sekolah Penggerak”at SMA 5 Negeri Kupang In each new teaching, the module changes according to the conditions of the students, but not only revision and development of teaching modules. The assessment of the results of the module development in this study was determined by two criteria, namely validity and practicality. Based on the assessment of the material expert, the average result was 80% with the appropriate criteria. The media expert assessment obtained an average result of 77% with the appropriate criteria. Thus the modules that have been developed in terms of materials and mediaare classified or can be said to be feasible modules to use. Based on the questionnaire the teacher's responses are an average of 88% with very feasible criteria and student responses, an average of 87% is obtained with very feasible criteria.